Technology-Enhanced Disaster Education for Early Childhood: Interactive Media to Build Safety and Resilience - Humaedi; Nirmala, Besse; Annuar, Haerul; Marwany; Agusniatih, Andi; Rizal (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
Early childhood is one of the most vulnerable groups during disasters, yet disaster education at this level is often overlooked. This lack of early preparedness can increase risks when emergencies such as earthquakes occur. To address this problem, this study developed a disaster learning model for early childhood that integrates disaster risk reduction into a contextual and enjoyable learning process. Using a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the research was conducted at TK Putra Kaili Permata Bangsa in Palu, involving 27 children aged 5–6 years. The model was designed through a play-based approach using child-friendly media such as videos, songs, storytelling, and a modified snakes-and-ladders game, structured in three stages: pre-play, during play, and post-play. Expert validation of instructional design, content, media, and language indicated high feasibility, with most aspects scoring above 80%. Effectiveness testing revealed significant improvements in children’s disaster preparedness across six key aspects, with N-Gain scores ranging from 0.59 to 0.74. These findings highlight the importance of introducing disaster education in early childhood, as the model not only strengthens safety and resilience but also offers a participatory and enjoyable strategy for disaster mitigation learning.